A clinical epidemiological study of 251 cases of amyotrophic lateral sclerosis in the south of Brazil Estudo clínico epidemiológico de 251 casos de esclerose lateral amiotrófica no sul do Brasil - Lineu Cesar Werneck; Ruth Bezerra; Octavio da Silveira Neto; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To study the clinical forms of amyotrophic lateral sclerosis (ALS) and the possible presence of risk factors in order to verify if there is any difference between cases in Paraná, Brazil. METHOD: We studied 251 cases, all of which fulfilled the diagnosis criteria proposed in El Escorial (WFN). Between 1977 and 2004, 157 male and 94 female patients were examined. RESULTS: 220 cases were classified as ALS-Spinal Onset (ALS-SO), 24 as ALS-Bulbar Onset (ALS-BO) and 7 as Familial ALS. The mean age at time of evaluation was 54.4±12.3 years, and symptoms had started 17.9±15.7months previously. In the group studied, statistical relationships were found between heavy occupations and males; previous surgeries and females; ALS-BO and dysphagia and dysarthria in females; and ALS-SO and males, cramps, weakness, muscle atrophy, hypertonia, increased deep tendon reflex and abnormal gait. CONCLUSION: The average age at time of evaluation was lower than that registered in the literature but similar to the Brazilian series. Domestic work and heavy occupations appear to be related to precocious perception of the symptoms by interference with daily functions. The socioeconomically higher classes seek medical care early. There was no relationship with exposure to toxic agents or trauma. OBJETIVO: Estudar as formas clínicas de esclerose lateral amiotrófica (ELA) e possíveis fatores de risco, a fim de verificar se existem diferenças entre os casos do Paraná, Brasil. MÉTODO: Estudamos 251 casos entre 1977 e 2004, que preencheram os critérios propostos em El Escorial (WFN), sendo 157 do sexo masculino e 94 do feminino. RESULTADOS: Foram classificados como ELA de início espinhal (ELA-IE) 220 casos, ELA de início bulbar (ELA-IB) 24 casos e 7 casos como ELA familiar. A idade média na avaliação foi 54,4±12,3 anos cujos sintomas iniciaram 17,9 ±15,7 meses antes. Foram encontradas relações estatísticas entre ocupação que demandam esforços físicos com homens; cirurgias prévias com mulheres; ELA-IB, disfagia e disartria, mulheres; ELA-IE, homens, câimbras, fraqueza, atrofia muscular, hipertonia, aumento de reflexos profundos e marcha anormal. CONCLUSÃO: A idade média na época da avaliação foi menor que a registrada na literatura, mas similar às séries brasileiras. Trabalhos domésticos e ocupações que demandam esforços físicos estão relacionados com a percepção precoce dos sintomas pelas inferências com as funções diárias. As classes sócio-econômicas melhores situadas procuram atendimento médico mais cedo. Não foram encontradas relações com a exposição a agentes tóxicos e traumatismos.